SÄRAT DWIKARANA Suntingan Teks dan Terjemahan - , YANIAR ISTRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is the result of philological study of SÄrat Dwikarana text. The text can be found in the Museum of Sonobudoyo Yogyakarta, with collection code PB C 75. The text written by Raden Pujaharja, contains human life behavior that acts based on two or more causes, and how someone communicates in the society. This text was written in the form of the Javanese script by using Javanese language and prose. This manuscript is a patchwork text as there are many additional material and corrections from its author. This research presents the edited text and the translation. The editing process uses diplomatic editing enabling the reads to follow the text as close as possible, as described in the source manuscript. The translation process uses a combination of word-to-word translation and literal translation.